Women and Confucian cultures in premodern China, Korea, and Japan - Ko, Dorothy, 1957-; Haboush, JaHyun Kim; Piggott, Joan R. (University of California Press, 2003)
Representing an unprecedented collaboration among international scholars from Asia, Europe, and the United States, this volume rewrites the history of East Asia by rethinking the contentious relationship between Confucianism and women. The authors discuss the absence of women in the Confucian canonical tradition and examine the presence of women in politics, family, education, and art in premodern China, Korea, and Japan.